Answer:
(h+9)⋅(h+2)
Explanation:
1.1 Factoring h2+11h+18
The first term is, h2 its coefficient is 1 .
The middle term is, +11h its coefficient is 11 .
The last term, "the constant", is +18
Step-1 : Multiply the coefficient of the first term by the constant 1 • 18 = 18
Step-2 : Find two factors of 18 whose sum equals the coefficient of the middle term, which is 11 . -18 + -1 = -19
-9 + -2 = -11
-6 + -3 = -9
-3 + -6 = -9
-2 + -9 = -11
-1 + -18 = -19
1 + 18 = 19
2 + 9 = 11 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, 2 and 9
h2 + 2h + 9h + 18
Step-4 : Add up the first 2 terms, pulling out like factors :
h • (h+2)
Add up the last 2 terms, pulling out common factors :
9 • (h+2)
Step-5 : Add up the four terms of step 4 :
(h+9) • (h+2)
Which is the desired factorization